Antimicrobial Emulsifier–Glycerol Monolaurate Induces Metabolic Syndrome, Gut Microbiota Dysbiosis, and Systemic Low‐Grade Inflammation in Low‐Fat Diet Fed Mice. Issue 3 (9th January 2018) - Jiang, Zengliang; Zhao, Minjie; Zhang, Hui; Li, Yang; Liu, Mengyun; Feng, Fengqin
Abstract : Scope: Glycerol monolaurate (GML) is widely consumed worldwide in the food industry and is considered safe, but for chronic diseases, supporting scientific data remain sparse. This study investigates whether dietary GML induces metabolic syndrome, gut microbiota dysbiosis, and systemic low‐grade inflammation. Methods and results: GML‐induced occurrence of metabolic syndrome, gut microbiota alterations, and systemic low‐grade inflammation are investigated. The results demonstrate that GML induced metabolic syndrome by significantly increasing the body weight, weight gain, food intake, body fat, fat droplet size and percentage of epididymal fat, serum triglycerides (TG), LDL, and atherogenic index, and decreasing the body muscle ratio, liver weight, and HDL, compared to the control (CON) group. Meanwhile, GML significantly changed the β‐diversity and composition of gut microbiota and upregulated the circulating levels of serum LPS, IL‐1β, IL‐6, and TNF‐α. Importantly, GML significantly decreased Akkermansia muciniphila and Lupinus luteus, and increased Bacteroides acidifaciens, Escherichia coli and the microbial DNA abundance of the ten predicated metabolism pathways involved in carbohydrate, amino acid, and lipid metabolism. Conclusion: Our results indicate that relatively low‐dose GML consumption promotes metabolic syndrome, gut microbiota dysbiosis, and systemic low‐grade inflammation, thereby calling for a reassessment of GML usage. Abstract : Glycerol monolaurate (GML) induced metabolic syndrome, gut microbiota dysbiosis, and circulating low‐grade inflammation by significantly increasing the body fat percentage and epididymal fat; exacerbating serum lipid profiles disorder and histopathologic abnormality of epididymal adipose tissue; changing the composition and metabolic function of gut microbiota; and upregulating the production of the serum lipopolysaccharides (LPS) concentration and circulating inflammatory cytokines mainly involved in IL‐1β, IL‐6, and TNF‐α. The dotted arrows represent a mechanism that requires further proof.